Optimalisasi Teknologi Digital untuk Menyusun Media Pembelajaran berbasis Gamifikasi di Madrasah - Sa’diyah, Zumrotus; Fitriyah, Dewi Niswatul; Rozi, Fahru; Rosyida, Fatia Ainur (Forum Kerjasama Pendidikan Tinggi, 2025)
Madrasah Ibtidaiyah Nurul Huda Temayang as one of the educational institutions that continues to strive to improve the quality of learning well, one of which is by completing learning facilities such as digital TV in each class, wifi network, sound audio etc. Which is expected to be a support system for digital learning. However, in its use there are obstacles so that learning is not optimal due to the limitations of teachers in compiling digital-based learning media and utilizing YouTube as a means of learning media so that learning is not optimal. Therefore, there is a need for mentoring for teachers at MI Nurul Huda Temayang on the preparation of learning media that utilizes digital technology that integrates the Kodulor platform, word wall, google sites into gamification-based learning media. This activity aims to improve the competence of MI Nurul Huda Temayang teachers in utilizing digital technology to design interactive and interesting learning media, producing gamification-based learning media products that can be used directly in the learning process in the classroom and increasing student motivation and learning participation through the application of more interactive learning media. The results of the mentoring show a significant increase as evidenced by the ability to create digital media. Before mentoring, only 20% of teachers were able to create simple digital media. After the activity, 93% of teachers succeeded in creating at least one gamification-based learning media product using the Kodulor platform, word wall, and Google Sites, while the level of participant satisfaction based on the evaluation questionnaire, 94% of participants stated that they were satisfied with the materials and mentoring methods provided.